2021
DOI: 10.1002/jcb.29952
|View full text |Cite
|
Sign up to set email alerts
|

The role of BAG3 in health and disease: A “Magic BAG of Tricks”

Abstract: The multi‐domain structure of Bcl‐2‐associated athanogene 3 (BAG3) facilitates its interaction with many different proteins that participate in regulating a variety of biological pathways. After revisiting the BAG3 literature published over the past ten years with Citespace software, we classified the BAG3 research into several clusters, including cancer, cardiomyopathy, neurodegeneration, and viral propagation. We then highlighted recent key findings in each cluster. To gain greater insight into the roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 159 publications
(294 reference statements)
1
18
0
Order By: Relevance
“…Human BAG3 is 575 amino acids in length and has a molecular mass of 74 kDa [ 32 ], mainly seen in the cytoplasm [ 33 ]. Previous studies have indicated that BAG3 is involved in various cardiovascular diseases, such as myocardial hypertrophy, dilated cardiomyopathy, and chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Human BAG3 is 575 amino acids in length and has a molecular mass of 74 kDa [ 32 ], mainly seen in the cytoplasm [ 33 ]. Previous studies have indicated that BAG3 is involved in various cardiovascular diseases, such as myocardial hypertrophy, dilated cardiomyopathy, and chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…BAG3 is a co-chaperone binding to the ATPase domain of heat shock protein Hsc70/Hsp70 and regulating its chaperone function [209]. BAG3 is structurally organized in an Nterminal tryptophan-tryptophan (WW) domain, two IPV domains, two 14-3-3 binding motifs, a proline-rich region and a C-terminal BAG domain [210,211]. The protein-protein interaction of BAG3 with Hsc70/Hsp70 is mediated by its BAG domain [212].…”
Section: Bcl2 Associated Athanogene 3 (Bag3)mentioning
confidence: 99%
“…BAG3 is a co-chaperone binding to the ATPase domain of heat shock protein Hsc70/Hsp70 and regulating its chaperone function [200]. BAG3 is structurally organized in a N-terminal tryptophan-tryptophan (WW) domain, two IPV domains, two 14-3-3 binding motifs, a proline-rich region and a C-terminal BAG domain [201,202]. The protein-protein interaction of BAG3 with Hsc70/Hsp70 is mediated by its BAG domain [203].…”
Section: Bcl2 Associated Athanogene 3 (Bag3)mentioning
confidence: 99%